Stereotactic body radiation therapy for mediastinal lymph node metastases: how do we fly in a 'no-fly zone'?. (2nd November 2018) - Jereczek-Fossa, Barbara Alicja; Muto, Matteo; Durante, Stefano; Ferrari, Annamaria; Piperno, Gaia; Fodor, Cristiana; Comi, Stefania; Ricotti, Rosalinda; Garibaldi, Cristina; Dicuonzo, Samantha; Mazza, Stefano; Golino, Federica; et al.
Abstract: Purpose: To evaluate the treatment-induced toxicity (as primary endpoint) and the efficacy (as secondary endpoint) of stereotactic body radiation therapy (SBRT) in the treatment of mediastinal lymph nodes (LNs) in the so-called no-fly zone (NFZ) in cancers with various histology. Material and methods: Forty-two patients were retrospectively analyzed. Institutional dose/volume constraints for organs at risk (OARs) derived by published data were strictly respected. The correlation between treatment-related variables and toxicity was investigated by logistic regression, Chi-squared test or Fisher's exact test. Overall survival (OS), cause-specific survival (CSS), progression-free survival (PFS) and local control (LC) were collected from the follow-up reports. The impact of potential predictive factors on LC, PFS and OS were estimated by Cox proportional-hazard regression. Results: Median follow-up time was 16 months (range 1–41). Four patients had esophageal G1 toxicity. Ten and six patients had G1 and G2 pulmonary toxicity, respectively. Treatment site and irradiation technique were significantly correlated with G ≥ 2 and G ≥ 1 toxicity, respectively. OS probability at 19 months was 88.3% and corresponded to CSS. LC probability at 16 months was 66.3% (median LC duration: 22 months, range 1–41). Fifteen patients (35.7%) were disease-free at 25 months (median time, range 1–41). The biologically effective dose (BED) and the target dose coverage indexes were significantly correlated with LC. Conclusions: SBRT can be considered as a safe treatment option for selected patients with oligo-metastases/recurrences in the NFZ, if strict dose/volume constraints are applied.